Critical Analysis of the Nucleus–Plasma Scheme and Community Plasma from the Perspective of Community Economic Growth and Business Law - Somomoeljono, Suhardi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The plantation sector, particularly palm oil plantations, is one of the strategic sectors in Indonesia's economic development. The policy of granting Plantation Business Licenses (IUP) and Land Cultivation Rights (HGU) to plantation companies is essentially accompanied by an obligation to develop community plasma plantations amounting to at least 20% of the total cultivated land area. However, in practice, the implementation of this community plasma policy has not fully provided a significant impact on improving the welfare of communities surrounding plantation areas. This study aims to critically examine the relationship between plantation companies as the nucleus and local communities as plasma from the perspective of community economic growth and business law. The research method used is a normative juridical approach with deductive-descriptive analysis of legal policies governing plantations and the management of community plasma schemes. The findings indicate that weak legal policies and the lack of optimal government supervision are the primary factors causing the ineffective implementation of community plasma obligations. Therefore, the establishment of a special institution with national authority, such as the National Authority Agency for Indonesian Plantation Plasma (BONPPI), is necessary to supervise, coordinate, and ensure the implementation of community plasma obligations in a fair and transparent manner. The existence of such an institution is expected to improve community welfare, strengthen people's economic empowerment, and support equitable national economic growth.